Manajemen Hipertensi Dengan Terapi Komplementer: Jahe dan Daun Mint - Lannasari Lannasari; Solehudin Solehudin; Emi Yuliza; Novrida Tambunan (Faedah : Jurnal Hasil Kegiatan Pengabdian Masyarakat Indonesia, 2023)
Hypertension is the main cause of death from cardiovascular diseases such as heart attacks, strokes and heart failure. The prevalence of hypertension is increasing rapidly in many countries, placing a large health burden on the health care system and increasing the risk of cardiovascular disorders in this population. The process of implementing community service to the community is carried out in several stages. Activities include checking blood pressure, health education and health consultations. Participants who took part in community service activities were mostly women (76%) with an age range between 45-60 years (68%), the highest education level was junior high school (42%), and people with hypertension level 1 (74%). Community knowledge about hypertension complementary therapy has increased significantly after being given counseling. Hypertension sufferers are advised to consume ginger and mint decoction and check themselves regularly at the nearest health facility.